PENGARUH HARGA DAN KERAGAMAN PRODUK DALAM MENENTUKAN KEPERCAYAAN KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO SEMBAKO SYAFA SYAFI DI ASEMBAGUS SITUBONDO - Anggara, Awangga Leo; Soeliha, Siti; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is an activity that must be carried out by a company, both goods and services companies in an effort to gain profits and maintain the viability of the company. The purpose of this study was to analyze and examine the effect of Price and Product Diversity in Determining Consumer Trust with Consumer Satisfaction as an Intervening Variable at the Syafa-Syafi Asembagus Grocery Store. The sampling technique was determined by the simple random sampling method. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that price (X1) has a significant positive effect on consumer satisfaction (Y1), thus Hypothesis 1 is accepted. Product diversity (X2) has a significant positive effect on consumer satisfaction (Y1), thus Hypothesis 2 is accepted. Price (X1) has a significant positive effect on consumer confidence (Y2), thus Hypothesis 3 is accepted. Product diversity (X2) has a negative but not significant effect on Trust (Y2), thus Hypothesis 4 is rejected. Consumer satisfaction (Y1) has a significant positive effect on consumer confidence (Y2), thus Hypothesis 5 is accepted. Price (X1) on consumer confidence (Y2) through consumer satisfaction (Y1) has a significant positive effect, thus Hypothesis 6 is accepted. Product diversity (X2) on consumer confidence (Y2) through consumer satisfaction (Y1), has a significant positive effect, thus Hypothesis 7 is accepted.